Ground beam construction / Fairuz Ithnin - Ithnin, Fairuz (Universiti Teknologi MARA, Perak, 2014)
This report is based on observation and experience for five months on a construction site. This report will include, with the introduction, company background, case studies, conclusions and recommendations. This report also deals with the way to do the job at a construction site, especially the structure. The structure chosen is ground beams. This report will describe the process, or the way bow to do is work to make ground beam quality. A ground beam is a reinforced concrete beam for supporting walls, beams, etc., on or near the soil surface, itself, either directly resting on the ground or supported on both ends. This report will also describe the process or supplier that will be used to process works this ground beams incident. ground beams are usually not a problem but a problem making the materials used to make ground beams themselves as problems such as plywood used time to expand too quickly or brittle when exposed to the rain and others. This report will tell the solution that will be taken and will distinguish between the different materials used in construction site "Projek Perumahan Mampu Milik 2 Tingkat, Mutiara Rini".